Upaya Peningkatan Perilaku Pencegahan KEK (Kurang Energi Kronis) pada Ibu Hamil di UPT Puskesmas Dolo Kabupaten Sigi Sulawesi Tengah - Reni Yuli Astutik; Putri Serenggu (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Chronic Energy Deficiency (CED) is a nutritional problem in pregnant women caused by a prolonged lack of energy intake. The prevalence of CED among pregnant women in Central Sulawesi Province has been recorded at 2,449 cases, with Sigi Regency ranking third highest with a prevalence of 3.25%. The long-term impacts of CED on pregnant women include the risk of maternal death, chronic anemia, and hemorrhage. For the fetus/child, the impacts include stunting, low birth weight, and intellectual disabilities. Many pregnant women still have limited knowledge regarding balanced nutrition during pregnancy, which may affect the health of both mother and baby. In 2025, there were 189 pregnant women with CED (14.41%) recorded in the working area of UPT Dolo Public Health Center. A community service program in the form of education on CED prevention and management was conducted at the Posyandu in Kotapulu Village, Sigi District, Sigi Regency. The results showed an increase in pregnant women's knowledge by 77.8%.